2013
DOI: 10.1111/acv.12059
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying how territory quality and sociobiology affect recruitment to inform fire management

Abstract: The combined effects of habitat quality, breeder experience and sociobiology on population demography are poorly understood. Natural fire regimes, which influence habitat quality and sociobiology, have been replaced by controlled fire management in most ecosystems. Managing fire mosaics (vegetation at different ages since fire) can be important to sustain species in fire-maintained habitats, but requirements are usually poorly defined. Source-sink theory provides a foundation to quantify such habitat heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Funding for conducting prescribed fires is often specified for fuel management and not necessarily for species habitat management; administrators from agencies often measure the performance of prescribed fire programs using the acreage burned each year, which provides little information on scrub habitat quality trajectories, because fire intensity and outcomes are heterogeneous [10]. Our studies have shown that an emphasis on fuel management will not achieve species conservation goals on many conservation lands [9,18].…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Funding for conducting prescribed fires is often specified for fuel management and not necessarily for species habitat management; administrators from agencies often measure the performance of prescribed fire programs using the acreage burned each year, which provides little information on scrub habitat quality trajectories, because fire intensity and outcomes are heterogeneous [10]. Our studies have shown that an emphasis on fuel management will not achieve species conservation goals on many conservation lands [9,18].…”
Section: Introductionmentioning
confidence: 95%
“…Many ecologists agree that burning more frequently might hasten returning degraded scrub to a more desired ecological state [10], but this would require significant management effort and willingness to value mosaic fires for ecological benefit. Fire managers recognize that mosaic fires are difficult to achieve and observe that burning early in the vegetation recovery cycle often achieves less reduction in fuels than waiting until fuels become mature and more continuous.…”
Section: Management Of Florida Scrub: Fuel Management Vs Ecological mentioning
confidence: 99%
See 3 more Smart Citations